What are universities pursuing? A review of the Quacquarelli Symonds world university rankings of Taiwanese universities (2021–2023) - Wang, Ru-Jer; Shih, Yi-Haung (Frontiers in Education, 2023)
This study evaluated world university rankings in Taiwan. Media reports and the literature on world university rankings have focused on rankings, particularly in Taiwan. This study conducted a document analysis of the Quacquarelli Symonds (QS) World University Rankings in Taiwan’s universities from 2021 to 2023, and explored two cases: National Taiwan University and Taipei Medical University, both of which are listed in the QS World University Rankings for sustainable development. First, the researchers analyzed the related topics of the world university rankings. Second, the researchers explored the position of Taiwan's universities in relation to the top 500 universities in the QS World University Rankings from 2021 to 2023. Third, two case universities pursuing QS World University Rankings are discussed. Finally, this study found that both universities are improving their teaching, research, and internationalization based on the indicators of the QS World University Rankings and the development of school affairs. The universities employ international faculty, cooperate internationally on projects, developing cross-disciplinary research, strengthening innovation, and increasing internationalization and cooperation with research institutions, and attract foreign students for sustainable development. The findings may serve as a reference for improving QS World University Rankings and promote the sustainable development of Taiwan’s higher education system, and understand global competition among universities.